2003
DOI: 10.2169/internalmedicine.42.244
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Lipoprotein Profile by Polyacrylamide Gel Disc Electrophoresis

Abstract: Objective We studied the relationship between the polyacrylamide gel electrophoresis (PAGE) pattern of lipoproteins and other indicators of lipid metabolism. Materials and Methods Fasting serum lipid was analyzed in 108 Japanese hyperlipidemic and normolipide-mic subjects (39 males and 69 females, 63.5±6.4 years old). We classified the lipoprotein profile by PAGEinto the following four types (SAND); Type S (symmetric), Type A (asymmetric), Type N (nodular), and Type D (disrupted). The relationship between WHOc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 13 publications
1
14
0
Order By: Relevance
“…In a previous study, we classified the lipoprotein profile by polyacrylamide gel electrophoresis into four types (SAND), type S (symmetric), type A (asymmetric), type N (nodular), and type D (disrupted), and we showed that the SAND classification of the lipoprotein profile may offer a new clinical tool to cover the weak points of the WHO classification, particularly in relation to the presence of a midband (5). We also suggested that the TC/ TG ratio may be a simple and useful marker of SAND types.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…In a previous study, we classified the lipoprotein profile by polyacrylamide gel electrophoresis into four types (SAND), type S (symmetric), type A (asymmetric), type N (nodular), and type D (disrupted), and we showed that the SAND classification of the lipoprotein profile may offer a new clinical tool to cover the weak points of the WHO classification, particularly in relation to the presence of a midband (5). We also suggested that the TC/ TG ratio may be a simple and useful marker of SAND types.…”
Section: Introductionmentioning
confidence: 93%
“…The blood samples used in the present study were the same as those used in the previous study (5). However, some special cases such as hyper-HDL-cholesterolemia and LCAT deficiency were excluded.…”
Section: Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…PAGE of lipoprotein fractions was performed using the LipoPhor system (Joko, Tokyo, Japan) as described previously 4) . The LDL-migration index (LDL-MI) was calculated as described by Mishima et al 6) as the distance between the very low-density lipoprotein (VLDL) peak and the LDL peak divided by the distance between the VLDL peak and the HDL peak.…”
Section: Lipoprotein Analysismentioning
confidence: 99%
“…In a previous study, we classified lipoprotein profiles by polyacrylamide gel electrophoresis (PAGE) and showed that this classification may offer a new clinical tool to make up for the weak points in WHO classification, particularly in relation to the presence of a midband 4) . We also proposed the usefulness of serum total cholesterol (TC)/TG and LDL-C/TG ratios for predicting the presence of small, dense LDL as a simple indicator 5) .…”
Section: Introductionmentioning
confidence: 99%